Neurostimulating control of the blocks of medial branches of posterior rami of spinal nerves in treatment of the “pain facet syndrome” of lumbar spondyloarthritis and planning of denervation of zygapophysial joints - Перфільєв, Олександр Вячеславович (ScienceRise: Medical Science, 2016)
The aim of research is an improvement of blocks of medial branches of posterior rami of spinal nerves (MB PR SN) in treatment of the “pain facet syndrome” of lumbar spondyloarthritis and planning of denervation of zygapophysial joints by the additional identification of target nerves by neurostimulator. Material and methods. 96 patients with lumbar “facet syndrome” (40 men and 56 women) 18 -75 years old. All patients underwent blocks of MB PR SN under “С-arm” control and electrostimulation by “B BRAUN Stimuplex Dig RC Nerve Stimulator”. The effectiveness of MB PR SN blocks was evaluated during a week, in 1, 3, 6 and 12 months by VAS and questionnaire Roland-Morris. Results of research. At the beginning 524 blocks were done at the level L3-S1 in 96 (100 %) patients. 420 blocks in 70 patients at the levels L3-L4, L4-L5, L5-S1, and 104 ones in 26 patients at the levels L4-L5, L5-S1. The positive dynamics was observed during 3 months with decease of pain syndrome from 50 % to 72 %, and improvement of living activity from 50 % to 67 %. In 54 patients (56 %), the blocks were repeated at 7 day. That is 270 blocks in 45 patients at the levels L3-L4, L4-L5, L5-S1, and 36 blocks in 9 patients at the levels L4-L5, L5-S1. The positive dynamics was observed during 6 months with decrease of pain syndrome from 50 % to 58 %, and improvement of living activity from 38 % to 63 %. MB PR SN neurotomy was done in 18 patients (18,7 %) after two blocks under endoscopic control with decrease of pain syndrome by 63 %-86 % depending on age and improvement of living activity by 50 % - 75 % more than 1 year. Conclusion. Electric stimulation of multi-sectional muscles during MB PR SN blocks allows reliably identify the necessary nerve rami, decrease the falsely positive and falsely negative results at anatomic variation of nerves location that gives a reason for using this method for both treatment of pain facet-syndrome and planning of ZJ denervation in patients with lumbar spondyloarthritis